Protein Purification Principles and Practice - Scopes, Robert K (Springer Advanced Texts in Chemistry., 1994)
A guide providing a brief account of the main protein fractionation methods, with some simple theoretical and thermodynamic explanations of the events occurring, for students and researchers involved in the process of isolating an enzyme, from whatever source. A basic background in biochemistry and protein chemistry is assumed.